Implementasi Location Based Service Pada Sistem Presensi Geolokasi Berbasis Web - Syamaidzar, Fata Nurlaudza' 'aza; Sutopo, Joko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Currently, attendance recording for the Narawungngi Dasandriya Student Choir is conducted manually using a attendance calendar. This method poses challenges, such as members occasionally forgetting to bring the attendance calendar, resulting in difficulties for the membership division to accurately record attendance. Consequently, the attendance recording process becomes less effective. Therefore, the implementation of an attendance system is necessary to enhance the efficiency of this process. The geolocation-based attendance system at the Narawungngi Dasandriya Student Choir is a web-based system utilizing Location Based Service information. It leverages geolocation features as a means of verifying member positions, aiming to improve the efficiency of attendance recording conducted by members. The development of this system follows a waterfall method, progressing incrementally from needs analysis, design, and planning to application testing using black box testing. Based on the outcomes of the implemented method and system testing, the constructed geolocation attendance system aids members in attendance registration and assists the membership division in recording attendance, thereby enhancing the efficiency of the attendance process.